Effect of medication adherence on renal allograft outcome in postkidney transplant patients - Sornhiran, Panthita; Ingsathit, Atiporn; Phakdeekitcharoen, Bunyong; Sumethkul, Vasant; Kantachuvesiri, Surasak; Arpornsujaritkun, Nuttapon; Sakulchairungrueng, Bundit (Journal of the Nephrology Society of Thailand, 2022)
Background: Assessing medication adherence among patients postkidney transplant is vital to provide the best chance for kidney survival following transplantation. Currently, the immunosuppressant therapy adherence instrument (ITAS) is the only validated questionnaire that is widely used among Western patients after organ transplant. However, this tool has never been used in Thailand. Methods: This study was divided in 2 phases. First, a cross-sectional study was conducted to validate the Thai-version ITAS in a small group of patients postkidney transplant using Cronbach’s coefficient was employed to determine the reliability of the questionnaire. Second, a retrospective cohort study was conducted to determine the effect of medication adherence on primary composite renal graft outcome, including graft failure, graft rejection, GFR decline >50% or biopsy-proven interstitial fibrosis and tubular atrophy (IFTA), among patients postkidney transplant. Kaplan-Meier was applied to determine incidence of composite graft outcomes in both groups. Multivariate Cox regression was applied to assess the factors associated with medication adherence, and renal allograft outcome. Results: In Phase I, ITAS was validated in among 40 patients postkidney transplant. Cronbach’s coefficient of the validated Thai version ITAS was 0.88. In Phase II, 198 patients postkidney transplant were enrolled to assess medication adherence using the validated Thai-version ITAS. In this study, 153 (77.27%) patients achieved good adherence (ITAS score = 12) while, 45 (22.73%) exhibited poor adherence (ITAS score <12). No significant difference was found in baseline characteristics among patients between both groups and no factor significantly correlated with medication adherence. Kaplan-Meier analysis showed higher incidence of composite renal allograft outcome among patients with good adherence compared with poor adherence. From multivariate analysis, factors associated with composite graft outcome included AKI donor, ECD donor, and poor medical adherence (ITAS score <12) with adjusted hazard ratio 4.00 (95%CI 1.25-12.86), 4.11 (95%CI 1.28-13.19), and 4.05 (95%CI 1.42-11.54), respectively. Conclusion: Assessing patient medication adherence using feasible and reliable tools is vital to achieve treatment goal providing the best chance for kidney survival and function.